Corporate As a Criminal Act of Corruption in Indonesia - Dia Lizza Elina; Budi Parmono; Rahmatul Hidayati (Budapest International Research and Critics University, 2022)
In Indonesia, corruption is widely accepted as an epidemic disease, some even consider it to have become a societal culture. Corruption in Indonesia today is systemic and endemic so that it is not only detrimental to state finances and the country's economy but has also violated the economic and social rights of the wider community. The existence of a corporation as a legal subject has a very important role in the development of a country. So that corporations have the potential to commit deviant acts and lead to criminal acts. The punishment of corporations is different from the punishment of people, because corporations have a different character in principle from the criminal law subject of people. Corruption in Indonesia has penetrated into all aspects of life, to all sectors, to all levels. In this study, the authors formulate several problem formulations, namely regarding the regulation of criminal acts of corruption by corporations, corporate responsibility as perpetrators of criminal acts of corruption, and sanctions or punishment of corporations as perpetrators of corruption. This study uses a normative legal research method, and by using a statutory approach and a philosophical legal approach. The results of the research obtained are that normatively, it has outlined provisions other than individuals, corporations are also legal subjects who can be charged with corruption. With the stipulation of a corporation as a legal subject, rights and obligations arise in it, so if a corporation commits a criminal act of corruption, it must be viewed as a Person who can be held accountable. And also later the imposition of sanctions or crimes against corporations that legally commit a criminal act of corruption, for the determination of sanctions for corporations that commit criminal acts of corruption there are several ways, among others, imposing fines on corporations and revocation of business licenses.